1993
DOI: 10.1016/0014-5793(93)80279-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel ryanodine sensitive calcium release mechanism in cultured human myometrial smooth‐muscle cells

Abstract: In cultured human myometrial cells application of caffeine (1–30 mM) did not result in an elevation of intracellular Ca2+ ([Ca2+]i). Caffeine was found to reversibly inhibit both spontaneous and agonist‐induced repetitive rises in [Ca2+]i possibly as a consequence of its ability to interfere with the binding of inositol trisphosphate (IP3) to the receptor on the sarcoplasmic reticulum. Brief applications of ryanodine (1–10μM) were observed to elevate [Ca2+]i and repeated exposures to ryanodine could elicit Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
1
29
1
1
Order By: Relevance
“…For example, fura-2 and 45 Ca 2ϩ efflux measurements revealed that Ca 2ϩ release from intracellular stores of human uterine smooth muscle cells was ryanodine-sensitive but caffeine-insensitive (62,63). In addition, ryanodine caused an increase in intracellular Ca 2ϩ concentrations in human Jurkat T-lymphocytes that express RyR3, but caffeine did not (64).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fura-2 and 45 Ca 2ϩ efflux measurements revealed that Ca 2ϩ release from intracellular stores of human uterine smooth muscle cells was ryanodine-sensitive but caffeine-insensitive (62,63). In addition, ryanodine caused an increase in intracellular Ca 2ϩ concentrations in human Jurkat T-lymphocytes that express RyR3, but caffeine did not (64).…”
Section: Discussionmentioning
confidence: 99%
“…Microspectrofluorimetry of intact cultured myometrial cells with Fura-2 suggested that a ryanodine-sensitive, caffeine-insensitive Ca 2+ release mechanism may be operational [8]. In order to directly demonstrate a caffeine-insensitive, ryanodine-sensitive Ca 2+ release activity, the non-mitochondrial stores of permeabilised human myometrial cells were loaded with 45Ca 2+.…”
Section: Effects Of Ryanodine and Caffeinementioning
confidence: 99%
“…Previous work on cultured human myometrial cells has demonstrated that a ryanodinesensitive Ca > release mechanism is operational [8] and preliminary studies indicate the expression and isolation of a ryanodine binding protein in both myometrial cultured cells and whole tissue [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reStudies in the rat vascular smooth muscle cell line A7r5 indicate ported that a ryanodine-sensitive, caffeine-insensitive Ca -,+ rethat the two receptors may operate functionally and spatially lease mechanism is present in intact human myometrial smooth distinct Ca 2÷ stores [28]. However, the use of this cell line may muscle cells [15]. Molecular cloning of RyR-specific transcripts require care in the interpretation of results obtained.…”
Section: Effect Of Ryanodine and Caffeine On 45ca2+ Releasementioning
confidence: 99%
“…Microspecinflux pathways and the mobilisation of Ca 2÷ from an intraceltrofluorimetry studies using intact myometrial smooth muscle lular Ca 2÷ store, the sarcoplasmic reticulum (SR). In human cells indicate that a ryanodine-sensitive but caffeine-insensitive uterine artery vascular smooth muscle cells agonists such as Ca 2+ release mechanism may be operational [15]. Therefore, to histamine can activate repetitive oscillations in intracellular investigate directly the activation of these complex responses Ca 2+ in the absence of external Ca 2÷ [1].…”
mentioning
confidence: 99%